THE IMPACT OF ISLAMIC EDUCATION BASED SOCIAL EMOTIONAL LEARNING ON IMPLEMENTING THE INDEPENDENT CURRICULUM IN TEMBILAHAN ELEMENTARY SCHOOLS - Nurlaila, Nurlaila; Bte Salman, Nola Fibriyanti (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Purpose: This study aims to analyze the influence of Social Emotional Learning (SEL) based on Islamic Education on the implementation of the Independent Curriculum in elementary schools within the Panglima Sulung Cluster, Tembilahan. Method: The research employed a quantitative correlational approach involving 196 respondents, consisting of teachers and students from SDN 001 Tembilahan Kota and SDN 002 Tembilahan. Result: The findings reveal a positive and significant relationship between Islamic Education–based SEL and the implementation of the Independent Curriculum (r = 0.672; p < 0.05). The coefficient of determination (R² = 0.451) indicates that 45.1% of the variance in the successful implementation of the Independent Curriculum is influenced by the application of Islamic value–based SEL. The integration of values such as sincerity (ikhlas), patience (sabr), trustworthiness (amanah), brotherhood (ukhuwah), and justice (‘adl) has been shown to support differentiated learning and strengthen the Pancasila Student Profile. Conclusion: This study confirms that Islamic Education–based SEL plays a strategic role in enhancing the effectiveness of the Independent Curriculum. Practically, these findings recommend the systematic integration of Islamic social-emotional and spiritual learning into the planning and implementation of teaching and learning processes in elementary schools.